Association of biomarkers with health-related quality of life and history of stressors in myalgic encephalomyelitis/chronic fatigue syndrome patients. Issue 1 (December 2016) - Fenouillet, Emmanuel; Vigouroux, Aude; Steinberg, Jean; Chagvardieff, Alexandre; Retornaz, Frédérique; Guieu, Regis; Jammes, Yves
Abstract Background Myalgic encephalomyelitis chronic fatigue syndrome (ME/CFS) is a common debilitating disorder associated with an intense fatigue, a reduced physical activity, and an impaired quality of life. There are no established biological markerof the syndrome. The etiology is unknown and its pathogenesis appears to be multifactorial. Various stressors, including intense physical activity, severe infection, and emotional stress are reported in the medical history of ME/CFS patients which raises the question whether any physiological and biological abnormalities usually found in these patients could be indicative of the etiology and/or the quality-of-life impairment. Methods Thirty-six patients and 11 age-matched healthy controls were recruited. The following variables that appear to address common symptoms of ME/CFS were studied here: (1) muscle fatigue during exercise has been investigated by monitoring the compound muscle action potential (M-wave); (2) the excessive oxidative stress response to exercise was measured via two plasma markers (thiobarbituric acid reactive substances: TBARS; reduced ascorbic-acid: RAA); (3) a potential inflammatory component was addressed via expression of CD26 on peripheral blood mononuclear cells; (4) quality-of-life impairment was assessed using the London Handicap Scale (LHS) and the Medical Outcome Study Short Form-36 (SF-36). The medical history of each patient, including the presence of stressors such as intense sports practice, severe acute infection and/or severe emotional stress was documented. Results We observed that: (1) there were striking differences between cases and controls with regard to three biological variables: post-exercise M-wave, TBARS variations and CD26-expression at rest; (2) each of these three variables correlated with the other two; (3) abnormalities in the biomarkers associated with health-related quality of life: the LHS score was negatively correlated with the exercise-induced TBARS increase and positively correlated with CD26-expression while the pain component of SF-36 was negatively correlated with CD26-expression; (4) the TBARS increase and the M-wave decrease were the highest, and the CD26-expression level the lowest in patients who had been submitted to infectious stressors. Conclusion In ME/CFS patients, severe alterations of the muscle excitability, the redox status, as well as the CD26-expression level are correlated with a marked impairment of the quality-of-life. They are particularly significant when infectious stressors are reported in the medical history.